The development strategy of sustainable regional level water management plan: an agenda for Bangladesh perspectives - Roxana Hafiz; Shariful A. Chowdhury; Sabera Sultana (2004)
In common with current global concerns over wise use and effective management of water, the Government of Bangladesh is committed to exploring, developing and using its water resources to the benefit of all users. To this end the Ministry of Water Resources published the first National Water Policy in 1999,whereas the paper focuses the Regional Water Management Plan (RWMP) with the intention of guiding both public and private actions in the future for ensuring optimal development and management of water that benefits both individuals and the society at large. This Paper aims to ensure progress towards fulfilling national goals of economic development, poverty alleviation, food security, public health and safety, decent standard of living for the people and protection of the natural environment. The Plan is presented in three phases: in the short-term (2000-05) it is considered a firm plan of ongoing and new activities; in the medium-term (2006-10) it is an indicative plan, and in the long-term (2011-25) a perspective plan. Implementation of the plan is to be monitored regularly and it will be updated every five years (IWRM, 2002). Water is central to the way of life in Bangladesh. Indeed, the river systems, many of which emanate from outside the country, have shaped much of the history, economy, literature and rich culture of the people. However, with a burgeoning population of 129 million expected to rise to 181 million by 2025 and to 224 million by 2050 (IWRM, 2002), the country faces many challenges ahead in an era of increasing globalization. Rapid urbanization is expected with 40% of people living in the towns and major cities by 2025, and 60% by 2050 (WARPO, 2001). Poverty is still endemic with over half the population classified as poor. In addressing these and other related issues, this paper sets new paradigms for the water sector, which include: decentralized water management; cost sharing and cost recovery; private sector participation; community participation; nontraditional financing modalities; regulation separated from supply; and new rights, obligations and accountability.